Advanced 3Y-TZP bioceramic doped with Al2O3 and CeO2 potentially for biomedical implant applications - Golieskardi M.; Satgunam M.; Ragurajan D.; Hoque M.E.; Ng A.M.H.; Shanmuganantha L. (Taylor and Francis Ltd., 2023)
Alumina; Aluminum oxide; Bioceramics; Biocompatibility; Biomechanics; Cell culture; Cell proliferation; Cells; Cerium oxide; Cytotoxicity; Mechanical properties; Morphology; Sintering; Vickers hardness; Yttria stabilized zirconia; Yttrium oxide; Zirconia; 3Y-TZP; Biomedical implant applications; Cell morphology; Operating temperature; Osteoblast cells; Sintering temperatures; Theoretical density; Yttria-stabilized zirconia (3Y-TZP); Fracture toughness